2017
DOI: 10.1007/s10142-017-0574-8
|View full text |Cite
|
Sign up to set email alerts
|

GILP family: a stress-responsive group of plant proteins containing a LITAF motif

Abstract: Lipopolysaccharide-induced tumor necrosis factor-α (LITAF) is a membrane protein that is highly dependent on correct location to exert transcription factor activity and protein quality control. In humans, LITAF, PIG7 (p53-inducible gene 7), and SIMPLE (small integral membrane protein of the lysosome/late endosome) refer to the same gene, which acts as a tumor suppressor. Several studies have shown that the transcription factor activity and nuclear translocation of LITAF protein are critical for the induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In the RRS, GILP had 44 additional unique co‐expressions in jub1 . Several previously identified co‐expressions of GILP with LSD1, AT4G34150, and NUDT7 (Cabreira‐Cagliari et al, 2018) were confirmed in the Col‐0 network “response to hypoxia.” Known co‐expressions of GILP with NUDT7 and AT4G34150 were not observed in jub1 but were present in mbf1c . Furthermore, GILP and NUDT7 were uniquely significantly co‐expressed with MBF1c in jub1 .…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In the RRS, GILP had 44 additional unique co‐expressions in jub1 . Several previously identified co‐expressions of GILP with LSD1, AT4G34150, and NUDT7 (Cabreira‐Cagliari et al, 2018) were confirmed in the Col‐0 network “response to hypoxia.” Known co‐expressions of GILP with NUDT7 and AT4G34150 were not observed in jub1 but were present in mbf1c . Furthermore, GILP and NUDT7 were uniquely significantly co‐expressed with MBF1c in jub1 .…”
Section: Discussionmentioning
confidence: 54%
“…Stress‐responsive GILP (Cabreira‐Cagliari et al, 2018) seems to be particularly important in deacclimation. In the RRS, GILP had 44 additional unique co‐expressions in jub1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation